2005
DOI: 10.1063/1.1874892
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flow evolution in swirl injector with radial entry. I. Stationary conditions

Abstract: The vortical flow dynamics in a gas-turbine swirl injector were investigated by means of large eddy simulations. The flow enters the injector through three sets of radial-entry, counter-rotating swirl vanes. The formulation treats the Favre-filtered conservation equations in three dimensions along with a subgrid-scale model, and is solved numerically using a density-based, finite-volume approach with explicit time marching. Several methods, including proper orthogonal decomposition, spectral analysis, and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 32 publications
5
34
0
Order By: Relevance
“…The PVC structure originates from the injector region and maintains its coherence till just downstream of the dump plane and partially wraps around the VBB. There is good qualitative agreement with past LES studies of premixed [25] and gaseous non-premixed [26] gas turbine combustors.…”
supporting
confidence: 83%
“…The PVC structure originates from the injector region and maintains its coherence till just downstream of the dump plane and partially wraps around the VBB. There is good qualitative agreement with past LES studies of premixed [25] and gaseous non-premixed [26] gas turbine combustors.…”
supporting
confidence: 83%
“…A positive pressure gradient is generated along the axial axis, which consequently leads to the formation of a recirculation zone, providing the swirl strength is high enough. Wang et al [85,108] performed an LES study of unsteady flow evolution in the radial-entry swirl injector shown in Fig. 10.…”
Section: Vortex Breakdownmentioning
confidence: 99%
“…Fig. 10 shows a typical radial-entry swirl injector [84,85], which consists of a mixing duct and a fuel nozzle located coaxially at the head end. Three radial-entry swirlers, counter-rotating with each other, are located at the entrance.…”
Section: Configurations Of Swirl Injectorsmentioning
confidence: 99%
“…Two swirled flows (Fig. 22(b) & (c)) were investigated by LES [242,243] to assess flow dynamics and more specifically the position and breakdown of the IRZ as discussed in details in [244]. A second example is shown on Fig.…”
Section: Swirler Simulationsmentioning
confidence: 99%